High Grazing Rates on Cryptophyte Algae in Chesapeake Bay - Johnson, Matthew D.; Beaudoin, David J.; Frada, Miguel J.; Brownlee, Emily F.; Stoecker, Diane K. (Frontiers in Marine Science, 2018)
Cryptophyte algae are globally distributed photosynthetic flagellates found in freshwater, estuarine, and neritic ecosystems. While cryptophytes can be highly abundant and are consumed by a wide variety of protistan predators, few studies have sought to quantify in situ grazing rates on their populations. Here we show that autumnal grazing rates on in situ communities of cryptophyte algae in Chesapeake Bay are high throughout the system, while growth rates, particularly in the lower bay, were low. Analysis of the genetic diversity of cryptophyte populations within dilution experiments suggests that microzooplankton may be selectively grazing the fastest-growing members of the population, which were generally Teleaulax spp. We also demonstrate that potential grazing rates of ciliates and dinoflagellates on fluorescently labeled (FL) Rhodomonas salina, Storeatula major, and Teleaulax amphioxeia can be high (up to 149 prey predator-1 d-1), and that a Gyrodinium sp. and Mesodinium rubrum could be selective grazers. Potential grazing was highest for heterotrophic dinoflagellates, but due to its abundance, M. rubrum also had a high overall impact. This study reveals that cryptophyte algae in Chesapeake Bay can experience extremely high grazing pressure from phagotrophic protists, and that this grazing likely shapes their community diversity.